Environmental Engineering (Laboratory) - Noorul Hudai Abdullah,; Norhayati Ngadiman,; Nor Baizura Hamid,; Hazirah Bujang,; Suhaila Sahat,; Muhammad Azraie Abdul Kadir, (2023)
The writers of this book as a guideline to understanding of the Environmental Engineering (Laboratory) version 2023 for the course DAC 12203 offered by the Centre of Diploma Studies (CeDS), Universiti Tun Hussein Onn Malaysia (UTHM). This book is divided into six (6) experiments and one (1) analysis: -i. Laboratory 1 Total Solid Determination (TSD) experiment to determine total solid content of water samples. In this experiment include Total Solid (TS), Total Suspended Solid (TSS), Total Dissolved Solid (TDS) and Volatile Suspended Solids (VSS)ii. Laboratory 2 Biochemical Oxygen Demand (BOD) experiment to measures the strength of the water sample (water, wastewater, etc.) based on the amount of oxygen needed to stabilize the organic matter in the sample.iii. Laboratory 3 Chemical Oxygen Demand (COD) experiment to determine the organic oxidizable matters content of water samplesiv. Laboratory 4 Jar Test experiment to determine the optimal coagulant dose which will produce the highest removal of a given water turbidity.v. Laboratory 5 Total Bacteria Count (TBC) experiment to measure the bacteriological quality of water sample using total plate count.vi. Laboratory 6 Ammoniacal Nitrogen (AN) experiment to measure the amount of nitrogen ammonia NH3-N of water samples using Nessler Method.vii. WQI analysis determine the water quality index for water samples.Diploma of civil engineering students will benefit from this book.